The economic impact of water diversion: evidence from China - Hang Xu; Rui Yang (Water Supply, 2024)
Many areas in the world are facing the problem of sustainable development due to water scarcity. One of the reasons for this issue is that the regional distribution of water resources is inequitable worldwide. The water diversion is a potential way to ease the water shortages as a result of the unequal distribution of water resources. As is well known, the South-to-North Water Diversion Project (SNWDP) in China is the largest project of water diversion over the world, which is transferring water resources between two river basins. This paper analyses the economic impact of the water diversion with the example of the SNWDP. It was found that the economic status of the areas affected by the SNWDP increased, relative to other regions. This result is robust when estimating with alternative outcome measure or subsample, and with alternative methods. The mechanism analysis shows that the main reason for the increased economic development level is that the water diversion encourages growth of the service industry in the water-receiving areas by supplying water for domestic use. These results imply that the sectors with more value-added may benefit better from the water diversion. HIGHLIGHTS The approach of Difference-in-Differences is used to examine the economic effects of water diversion.; After water diversion, the economic status in the areas that receive water increased.; By providing water, the water diversion supports the service sector in the water-receiving prefectures.;